2021
DOI: 10.1093/texcom/tgab039
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Analgesia Does Not Reduce Empathy for Naturalistic Depictions of Others’ Pain in a Somatosensory Specific Way

Abstract: The shared representations account postulates that sharing another’s pain recruits underlying brain functions also engaged during first-hand pain. Critically, direct causal evidence for this was mainly shown for affective pain processing, while the contribution of somatosensory processes to empathy remains controversial. This controversy may be explained, however, by experimental paradigms that did not direct attention towards a specific body part, or that did not employ naturalistic depictions of others’ pain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…More directly, by investigating the effect of causal manipulation of firsthand pain on empathy for pain, researchers observed that the firsthand placebo analgesia in the participant's right hand resulted in a comparable reduction of unpleasantness ratings for others' pain in both hands instead of a localized reduction for the right hand only. 56 This further suggests that shared affective representations play more of a role during empathy for pain compared with shared somatosensory representations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…More directly, by investigating the effect of causal manipulation of firsthand pain on empathy for pain, researchers observed that the firsthand placebo analgesia in the participant's right hand resulted in a comparable reduction of unpleasantness ratings for others' pain in both hands instead of a localized reduction for the right hand only. 56 This further suggests that shared affective representations play more of a role during empathy for pain compared with shared somatosensory representations.…”
Section: Discussionmentioning
confidence: 98%
“…31 Therefore, our result indicates that affect sharing plays a prominent role in empathy for pain, which coincides with recent functional magnetic resonance imaging (fMRI) studies investigating the shared representations between empathy for pain and firsthand pain. [55][56][57] For example, the activations in the AI and aMCC were stronger while participants observed others' facial expressions of genuine pain versus pretended pain; more importantly, the increased activation in the AI was selectively correlated with unpleasantness ratings for others' pain. 55 These results suggest that, in addition to the responses triggered by perceptual salience, the empathy-related brain responses also reflect the sharing of others' actual affective states triggered by pain.…”
Section: Discussionmentioning
confidence: 99%
“…The placebo groups’ belief in the effectiveness of the medication (Manipulation Check 3) was analyzed by calculating three paired-samples t tests comparing two of the three time points (before conditioning, after conditioning, after the session). Although these analyses were preregistered as exploratory, they were also employed in our previous studies using a very similar placebo analgesia induction with a gel instead of a pill (Hartmann, Riva, et al, 2021; Hartmann, Rütgen et al, 2021). On the basis of these studies, we expected a strong belief in the medication and an increased belief from before to after conditioning (see the Supplemental Material for exact criteria).…”
Section: Methodsmentioning
confidence: 99%
“…To measure whether the placebo effect lasted until the end of the session (Manipulation Check 5), we compared the postexperimental rating about how much pain was felt on average in the pain task using a t test with the index of pain ratings (pain – no pain) as the dependent variable and group (placebo, control) as a between-subjects factor. This check was not preregistered but was also employed in our previous studies (Hartmann, Riva, et al, 2021; Hartmann, Rütgen et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation